5 More Sleeps 'til Christmas - Fallon, Jimmy; Deas, Rich, 1969- (New York : Feiwel and Friends, 2020)
"Everyone who grew up celebrating Christmas remembers the excitement that built up to the most magical day of the year. But why not make the last week until Christmas more fun by counting how many sleeps until the arrival of Santa and his reindeer?"--Provided by publisher.
Keywords: Christmas stories; Bedtime -- Juvenile fiction; Christmas -- Fiction; Bedtime -- Fiction; Stories in rhyme; Stories in rhyme; Picture books; Christmas fiction